Ser2 from Serratia liquefaciens L53: A new heat stable protease able to destabilize UHT milk during its storage - Baglinière, François; Tanguy, Gaëlle; Salgado, Rafael Locatelli; Jardin, Julien; Rousseau, Florence; Robert, Benoît; Harel-Oger, Marielle; Vanetti, Maria Cristina Dantas; Gaucheron, Frédéric (Food Chemistry, 2017)
The heat-stable protease Ser2 is secreted by the species Serratia liquefaciens, a psychrotrophic bacteria frequently found in raw milk. To understand the physicochemical modifications of casein micelles induced by Ser2 and to confirm its implication in UHT milk destabilization, the enzyme was purified and added to microfiltered raw milk before UHT treatment. UHT milk destabilization was investigated during 90 days of storage. A visual destabilization appeared after 8 days of storage with the presence of sediment. Zeta potential increase and formation of aggregates were observed during the storage. Using tandem mass spectrometry, numerous released peptides from the four caseins were identified at the end of storage. Caseins were hydrolyzed in the preferential order b- > as1- > j- > as2. No specific peptidic hydrolysed bond was detected. The present study confirmed that the presence of the protease Ser2 in raw milk can be one of the main causes of UHT milk destabilization.
Keywords: Casein micelles; Ser2; UHT treatment; Stability; Proteolysis